2001
DOI: 10.1002/ijc.1422
|View full text |Cite
|
Sign up to set email alerts
|

Diet and ovarian cancer risk: A case-control study in Italy

Abstract: To assess the dietary correlates of cancer of the ovary, the consumption of a wide range of food groups has been investigated in a case-control study conducted between January 1992 and September 1999 in 4 Italian areas. Cases were 1,031 women with incident, histologically confirmed epithelial ovarian cancer; controls were 2,411 women admitted to the same network of hospitals as the cases for acute, non-malignant and non-gynecological conditions, unrelated to hormonal or digestive tract diseases or to long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
107
3
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 37 publications
(61 reference statements)
7
107
3
1
Order By: Relevance
“…Case -control studies on fruit consumption have yielded conflicting results. Although one study in China (Zhang et al, 2002) indicated a statistically significant inverse association between total fruit consumption and risk of ovarian cancer, four other studies found no association (Shu et al, 1989;Bosetti et al, 2001;McCann et al, 2001McCann et al, , 2003 and one study in Mexico (SalazarMartinez et al, 2002) reported a statistically significant positive association.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Case -control studies on fruit consumption have yielded conflicting results. Although one study in China (Zhang et al, 2002) indicated a statistically significant inverse association between total fruit consumption and risk of ovarian cancer, four other studies found no association (Shu et al, 1989;Bosetti et al, 2001;McCann et al, 2001McCann et al, , 2003 and one study in Mexico (SalazarMartinez et al, 2002) reported a statistically significant positive association.…”
Section: Discussionmentioning
confidence: 97%
“…All four case -control studies on total vegetable consumption and ovarian cancer risk have reported an inverse association (Bosetti et al, 2001;McCann et al, 2001McCann et al, , 2003Zhang et al, 2002). Case -control studies on fruit consumption have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence remains inconsistent; recent studies suggest that food items high in carotene and lycopene might decrease the risk [48], whereas red meat was associated with an elevated risk [49]. However, all positive studies were case-control studies, and a recent prospective study within the Nurses' Health Study found no association between the usage of vitamins/ carotenoids and ovarian cancer [50].…”
Section: Dietmentioning
confidence: 99%